The Challenge of the Regulation of Artificial Intelligence in the Judicial System and its Environment - Paulo Ramon SUAREZ XAVIER (Revista Jurídica Portucalense, 2022)
The present work seeks to analyse the most appropriate form of the legal regulation of the process of implementation of artificial intelligence in the Administration of Justice and its environment. To do this, it examines the concept of the justice ecosystem and analyses the regulatory proposals currently underway in the European Union, seeking to establish the appropriate legal framework for the intended purposes, capable of guaranteeing respect for fundamental rights, especially the right to an effective remedy and the requirements of the principle of legality.